2019
DOI: 10.1097/ico.0000000000001956
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcome Comparison Between Femtosecond Laser-Assisted and Manual Descemet Membrane Endothelial Keratoplasty

Abstract: Purpose: To evaluate 3-year outcomes of femtosecond laser-assisted Descemet membrane endothelial keratoplasty (F-DMEK) compared with manual Descemet membrane endothelial keratoplasty (M-DMEK) in patients with Fuchs endothelial corneal dystrophy (FECD). Methods: A retrospective, interventional study, including eyes with FECD and cataract that underwent either F-DMEK or M-DMEK combined with cataract extraction at either the Toronto Western Hospital or Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
1
32
0
1
Order By: Relevance
“…10 These outcomes are comparable to ours but are not as good as in other scenarios such as in patients undergoing DMEK for Fuch's endothelial dystrophy alone. 3,15 Nevertheless, significant BSCVA improvement was seen in our cohort, even in eyes that had visually limiting comorbidities. This could be clinically and functionally significant for such individuals who often suffer from bilateral low-vision.…”
Section: Discussionmentioning
confidence: 56%
“…10 These outcomes are comparable to ours but are not as good as in other scenarios such as in patients undergoing DMEK for Fuch's endothelial dystrophy alone. 3,15 Nevertheless, significant BSCVA improvement was seen in our cohort, even in eyes that had visually limiting comorbidities. This could be clinically and functionally significant for such individuals who often suffer from bilateral low-vision.…”
Section: Discussionmentioning
confidence: 56%
“…It may not be the filtrating effect that is decisive, but the mechanical effect of the GDD, which induces dysfunction of the endothelial cells. In eyes without graft failure, however, the endothelial cell loss after 36 months was 33.9%, which is in the normal range compared to other studies [30,32]. Other studies showed significant differences in endothelial cell loss between eyes with a previous glaucoma surgery and a control group only in the long-term follow-up [8,14,16], while especially GDD are well known for high endothelial loss rates [33].…”
Section: Graft Rejection and Graft Failurementioning
confidence: 58%
“…In a comparative study of 16 eyes with FECD, eyes that underwent F-DMEK had significantly less rate of postoperative graft detachment and consequently less number of rebubblings required. [ 155 ] Endothelial cell loss was significantly lower in the F-DMEK group till 2 years follow-up.…”
Section: Outcomes Of Dmek In Various Clinical Scenariosmentioning
confidence: 97%